Value of Diffusion-Weighted MRI in the Characterization of Cervical Lymphadenopathy in Head and Neck Tumors - Abdel-Mohsen , Aya Gamal; Shalaby , Shymaa Abdel-Mawla; Meselhy , Gehad Taha; Romeih, Marwa Abdel-Hamied (Journal of Neonatal Surgery, 2025)
Background: Apparent diffusion coefficient (ADC) is effective in distinguishing metastatic lymph nodes from benign lymph nodes. When ADC data are integrated with morphologic MRI, diagnostic results are significantly better than when MRI is assessed independently. We aimed to evaluate the diagnostic capabilities of diffusion-weighted (DW)-MRI and ADC values in distinguishing between benign and metastatic cervical lymph nodes Methods: This prospective study was conducted on 54 patients, afflicted with lymphadenopathy of the cervical region were examined. All patients were subjected to Diagnostic MRI scans of the neck and histological examination [Seven patients had excisional biopsies and forty-seven underwent fine needle aspiration cytology]. Results: A low ADC1000 was a significant lower in malignant persons compared to benign patients (P<0.001). Lymphoma patients had a significantly lower ADC1000 compared to malignant patients (P<0.001). ADC1000 effectively distinguishes malignant lymph nodes with high accuracy at cutoff of < 1.21, sensitivity of 94.1%, and specificity of 100%. For differentiating lymphoma patients, ADC1000 demonstrated excellent performance at a threshold of ≤ 0.91, with 100% sensitivity, 96.6% specificity. ADC1000 is a highly reliable imaging biomarker for distinguishing malignancies and lymphoma with remarkable diagnostic accuracy. Conclusions: The use of DW-MRI to evaluate cervical lymphadenopathy in patients with head and neck cancer offers promising results without invasive procedures. In a study of patients with head and neck cancer, DW-MRI showed remarkable diagnostic accuracy when used in conjunction with ADC data to distinguish between benign and metastatic cervical lymph nodes